The need for care and functionality among religious older women - Neuza Maria Sangiorgio Mozer; Adriano Pasqualotti; Marilene Rodrigues Portella (Universidade Federal de Goias, 2014)
The objective was to evaluate self-reported need for care and functionality among religious older women. It is a cross-sectional population-based survey. Data collection took place via a structured questionnaire containing sociodemographic information, self-reported need for care and assessment of functionality, through the Katz Index, which investigated independence in activities of daily living (ADL). The data were analyzed using Mann-Whitney U and chi-squared test, with a significance level of p ? 0.05 and a 95% confidence interval (CI). The following variables presented statistical significance: bathing, dressing and toileting. We conclude that although they reported the need for care, at most, our participants provide themselves with self-care. Evidence points to the need for more widespread studies on ageing in similar scenarios, for this process is progressive and expressive in religious congregations. doi: 10.5216/ree.v16i3.21589.